Hybrid RNA Sequencing Strategy for the Dynamic Transcriptomes of Winter Dormancy in an Evergreen Herbaceous Perennial, Iris japonica - Li, Danqing; Shao, Lingmei; Xu, Tong; Wang, Xiaobin; Zhang, Runlong; Zhang, Kaijing; Xia, Yiping; Zhang, Jiaping (Frontiers in Genetics, 2022)
Japanese iris (Iris japonica) is a popular perennial ornamental that originated in China; it has a long display period and remains green outdoors throughout the year. winter dormancy characteristics contribute greatly to the evergreenness of herbaceous perennials. Thus, it is crucial to explore the mechanism of winter dormancy in this evergreen herbaceous perennial. Here, we used the hybrid RNA-seq strategy including single-molecule real-time (SMRT) and next-generation sequencing (NGS) technologies to generate large-scale Full-length transcripts to examine the shoot apical meristems of Japanese iris. A total of 10.57 Gb clean data for SMRT and over 142 Gb clean data for NGS were generated. Using hybrid error correction, 58,654 full-length transcripts were acquired and comprehensively analysed, and their expression levels were validated by real-time qPCR. This is the first full-length RNA-seq study in the Iris genus; our results provide a valuable resource and improve understanding of RNA processing in this genus, for which little genomic information is available as yet. In addition, our data will facilitate in-depth analyses of winter dormancy mechanisms in herbaceous perennials, especially evergreen monocotyledons.